2022
DOI: 10.1038/s41598-022-09905-3
|View full text |Cite
|
Sign up to set email alerts
|

A novel wavelet decomposition and transformation convolutional neural network with data augmentation for breast cancer detection using digital mammogram

Abstract: Research in deep learning (DL) has continued to provide significant solutions to the challenges of detecting breast cancer in digital images. Image preprocessing methods and architecture enhancement techniques have been proposed to improve the performance of DL models such as convolutional neural networks (CNNs). For instance, the wavelet decomposition function has been used for image feature extraction in CNNs due to its strong compactness. Additionally, CNN architectures have been optimized to improve the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 46 publications
0
27
0
Order By: Relevance
“…The SVM result showed that the method yielded 89.24% and 97.19% for recall and precision, respectively. In our recent study 86 , we demonstrated the use of the wavelet function to optimize the selection process of suggestive features leading to classification accuracy. A hybrid algorithm involving seam carving and wavelet decomposition was experimented with for image preprocessing to find discriminative features.…”
Section: Related Workmentioning
confidence: 99%
“…The SVM result showed that the method yielded 89.24% and 97.19% for recall and precision, respectively. In our recent study 86 , we demonstrated the use of the wavelet function to optimize the selection process of suggestive features leading to classification accuracy. A hybrid algorithm involving seam carving and wavelet decomposition was experimented with for image preprocessing to find discriminative features.…”
Section: Related Workmentioning
confidence: 99%
“…ere are numerous approaches that have been anticipated for mammogram diagnosing. In general, they are can be grouped into statistical-based methods [13,14], waveletsbased methods [15][16][17], Markovian-based models [18], machine-learning-based methods [19], etc. Numerous investigations have been issued on computer breast cancer diagnosis.…”
Section: Literature Review and Related Workmentioning
confidence: 99%
“…The study investigated different transformational operations in achieving image synthesis on-the-fly to augment real images during training. In a recent study, (Olaide & Ezugwu, 2022) proposed the application of GAN-based data-augmentation approach to experiment on the performance of a CNN architecture with a novel wavelet function. Using the combination of MIAS and DDSM+CBIS datasets, the study showed that the classification of the network model yielded better classification and recall rate as compared with using the model without the augmentation method.…”
Section: Related Workmentioning
confidence: 99%
“…These methods have reported improved accuracy and recall with some values of 78% and 7.7% have been reported for both accuracy and recall rate respectively in some CAD-based systems (Freer & Ulissey, 2001). However, recent studies have shown that deep learning methods present more computational power to detecting the disease in medical images and identifying even very subtle abnormalities (Olaide & Ezugwu, 2022). Furthermore, the outstanding performance of deep learning method has motivated the use of CNN architectures to addressing the problem of classification of digital images for reduced false positive rate.…”
Section: Introductionmentioning
confidence: 99%